Factors Influencing the Duration of Acute Infantile Diarrhea - Rahardjo, Sutomo; Warouw, S. M. Salendu (Paediatrica Indonesiana, 2018)
A retrospective study was conducted on infantile diarrhea treated at the Gunung Wenang General Hospital to evaluate the relationship of age, nutritional status and cause of diarrhea to the duration of episode of infantile diarrhea. From January 1991 up to December 1992, 584 infantile diarrhea cases out of 1109 infants were treated at the Division Gastroenterology Child Health Department. Three hundred and forty-four (58,7%) of them were male, and 56% of patients were less than 12 months of age. The nutritional status was evaluated using NCHS standard; 391 (67,0%) were well-nourished, 49 (8,4%) were moderately under-nourished, and .S (0,8%) were severely malnourished. Duration of diarrhea of 4 days of less was found in 70.8% of patients 13-24 months old, 43.9% in 7-12 months age group, 46.2% of infants 4-6 months age group, and 54.8% of infants 1-3 months age group, 60,6% of well-nourished infants, 56,8% of mildly malnourished infants, and 31,5% of moderate to severely malnourished infants. Chronic diarrhea was found in 5 infants (0,9%), 3 with severe malnourished infants suffered from carbohydrate intolerance with E. histolytica infestation and the other 2 infants due to E. coli.